Status Hukum Akta Jual Beli Hak Milik Atas Tanah Bersertifikat yang Telah Dibatalkan Pengadilan Tata Usaha Negara - Kadek Indra Yuda; I Nyoman Putu Budiartha; Desak Gde Dwi Arini (Fakultas Hukum Universitas Warmadewa, 2020)
Buying and selling land is one of the legal acts that can cause the transfer of land rights from the hand of the seller to the buyer. The transition of land rights must be registered based on the evidence of the relevant deed. If traced from the beginning, there is a real buying and selling land arising based on an agreement or approval that is set in the form of a covenant between the seller and the buyer. Based on the background of this research problem is: how the existence of land-Buy sales certificate handled by PPAT certificate was cancelled and how the legal sanctions on Dibatalkannya legal status of PPAT deed in the purchase and Sale of land. The type of research used is empirical legal research. The results of the discussion in this study are: the existence of land purchase certificate that issued PPAT certificate was cancelled because PPAT is State Administration officer, in the event of a dispute, BPN is responsible for the certificate that has been Issued. PPAT has never come into contact with the TUN judiciary relating to the treaty Deed of ownership of the land. Guidelines for creating a certificate of land ownership in BPN. If the certificate is cancelled, the party that is won shall apply for the cancellation of the certificate to BPN, and juridically the PPAT deed that has been registered to the land Office is automatically null and void. Legal sanctions against the legal status of PPAT certificates and the sale of land, which have the same consequences as the unlawful act is only a violation of the law can be resolved through a public court, not Can be resolved through the State Administrative Court.